[preprint] Marques da Silva e Souto Moura: intervenções no Património no século XX | Marques da Silva and Souto Moura: interventions in the Patrimony in the 20th century - José Miguel Rodrigues (2022)
Architecture is an art which naturally tends towards action. It is in its genes, it is co-natural, something that was born with it. Thereby, perceived as an inborn tendency, it is at best excessive to condemn it for that. To act before what exists so that it becomes another reality. That is what is asked of it - and very often - it is exactly what is required - this constituting its way of being, like a survival instinct. Obviously, rigour and courage are also imposed on it, to propose inaction as a possibility, in other words, the audacity of renouncing, when facing the lack of need of the duty. In the eyes of common sense, this response - which for the craft is a matter of ethic and aesthetics regarding, what both share as architectonically substantial - is what is expected before what, briefly, is considered as patrimony. In the eyes of the craft, however, the matter implies the very discussion of the idea of patrimony, of its ways of conservation or preservation and, at the limit, of considering the relative value of what exists and is intended to be maintained as permanent, in comparisoned to what is proposed and will be accomplished, and which is also aimed at convincing the traditional hereditary policies (patrimonialists), could be described as the patrimony of the future.